THE RELATIONSHIP BETWEEN PATIENT EXPERIENCE AND PATIENT LOYALTY MEDIATED BY TRUSTWORTHINESS AND OUTCOME QUALITY IN HEALTHCARE SERVICES: A CASE AT PRIVATE CLINIC IN BATAM - Renaldo, Doddy; Antonio, Ferdi (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2024)
This study explores how patient experience influences patient loyalty, with trustworthiness and outcome quality as mediators. In Indonesia, health clinics have been segmented since introducing the national health insurance scheme called BPJS. While universal healthcare was achieved, some patients are willing to pay a premium for better care experiences. Understanding patient loyalty and its antecedents is crucial for maintaining a competitive advantage in private clinics. The study was conducted at a private clinic in Batam, involving 117 patients who visited between October and December 2023. Data were collected using a modified version of the GS-PEQ (Generic Short-Patient Experience Questionnaire) and further analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS4® software. Ten hypotheses were tested to explore the relationships between patient experience, trustworthiness, outcome quality, and patient loyalty. The findings reveal that patient experience positively impacts patient loyalty, which is mediated by trustworthiness. Outcome quality mediates the relationship between patient experience and trustworthiness but does not significantly mediate the relationship between patient experience and patient loyalty. This study highlights the importance of patient experience and trustworthiness in private clinics and suggests the use of GS-PEQ to measure patient experience and achieve competitive advantage.